(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To map the proposals and validity of instruments in Brazil to guide nursing consultations with adults in the pre- and post-operative stages of elimination stomas. Method: A scoping review recommended by JBI. The search took place without time or language limitations in the MEDLINE, IBECS, LILACS, CINAHL, Academic Search Premier and Scopus databases, using descriptors indexed in the Medical Subject Headings, such asNursing, Ostomy, Colostomy, Ileostomy, Patients, Practice guidelines, Preoperative Care, Postoperative Care, Validation studies, and the free term Urostomy, including gray literature. Results:of the 828 studies found, five were selected which aimed to: construct and validate an instrument (03); carry out cross-cultural adaptation and validate content (1); and analyze theoretical validity (1). All were the product of theses and dissertations published between 2013 and 2021. Dorothea Orem’s and Callista Roy’s theories guided four instruments. The postoperative phase was the only one addressed in all the instruments. Conclusion:the mapping showed Brazilian researchers’ interest in instrumentalizing nursing consultation for stoma patient, starting with instrument content validity. The results point to the need for studies aimed at clinical validity.